A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof
By preparing molybdenum-based lubricating composite materials containing SrMo5O8, the problem of poor friction and wear performance of existing lubricating materials at high temperatures is solved, and high-temperature lubricating performance with low friction coefficient and wear rate at 600°C is achieved.
Patent Information
- Application Number
- CN202310044331.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-01-30
AI Technical Summary
Existing lubricating materials have poor friction and wear performance at high temperatures, making it difficult to maintain stable lubricating performance in complex environments.
A molybdenum-based lubricating composite material containing SrMo5O8 is prepared by ball milling, press molding and vacuum hot pressing sintering to form a material with good high-temperature lubricating properties.
At 600°C, the molybdenum-based lubricated composite material containing SrMo5O8 exhibited a low coefficient of friction and wear rate, significantly improving the high-temperature lubricating performance.
Smart Images

Figure CN116219247B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricating materials, and in particular to a molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof. Background Art
[0002] New high-performance lubricating materials are one of the important guarantees for the stable and reliable operation of power transmission systems in high-tech fields such as aerospace, nuclear engineering, land transportation, machinery manufacturing, marine equipment, and energy. Metal-based solid lubricating composite materials are composed of a metal matrix and a solid lubricant, and the solid lubricant is evenly distributed in the metal matrix. Solid lubricants can form a lubricating film on the contact surface between high-tech moving parts, thereby avoiding direct contact between moving parts, achieving the effect of reducing friction and preventing wear.
[0003] The use environment of lubricating composite materials is often complex and changeable. However, at different temperatures, different lubricating composite materials show different lubrication properties. For example, the friction and wear properties of common solid lubricants such as graphite and MoS2 are easily affected by temperature. As the temperature rises, graphite oxidizes and loses its lubrication properties, while MoS2 oxidizes to form molybdenum oxide, which increases its friction coefficient. Therefore, it is of great significance to develop solid lubricants with good tribological properties at high temperatures. Summary of the invention
[0004] In view of this, the present invention aims to provide a molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof. The molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention has good high-temperature lubrication performance and low friction coefficient and wear rate at 600°C.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a molybdenum-based lubricating composite material containing SrMo5O8, which is prepared from the following raw materials in percentage by mass:
[0007] Molybdenum powder 85-97%;
[0008] Strontium sulfate 3-15%.
[0009] Preferably, it is prepared from the following raw materials in percentage by weight:
[0010] Molybdenum powder 90-95%;
[0011] Strontium sulfate 5-10%.
[0012] Preferably, the particle size of the molybdenum powder is 15 to 75 μm; the particle size of the strontium sulfate is 15 to 75 μm.
[0013] Preferably, the purity of the molybdenum powder is ≥99.5%, and the purity of the strontium sulfate is ≥99.7%.
[0014] Preferably, the mass percentage of the SrMo5O8 phase in the molybdenum-based lubricating composite material containing SrMo5O8 is 5.65-21.80%.
[0015] The present invention provides a method for preparing the above-mentioned molybdenum-based lubricating composite material containing SrMo5O8, comprising the following steps:
[0016] The molybdenum powder and strontium sulfate are ball-milled to obtain a mixed powder;
[0017] The mixed powder is pressed and vacuum hot-pressed in sequence to obtain a molybdenum-based lubricating composite material containing SrMo5O8.
[0018] Preferably, the ball milling is wet ball milling, the dispersion medium of the wet ball milling is ethanol, and the ball-to-material ratio is 5 to 15:1.
[0019] Preferably, the ball milling speed is 200-450 rpm and the time is 10-40 h.
[0020] Preferably, the compression molding pressure is 5 to 10 MPa and the time is 20 to 40 seconds.
[0021] Preferably, the vacuum hot pressing sintering temperature is 1100-1300° C., the pressure is 20-30 MPa, the heat preservation and pressure holding time is 30-120 min, and the heating rate is 5-15° C. / min.
[0022] Preferably, the vacuum degree of the vacuum hot pressing sintering is ≤1.0×10 -2 Pa.
[0023] The present invention provides a molybdenum-based lubricating composite material containing SrMo5O8, which is prepared from the following raw materials in percentage by mass: 85-97% molybdenum powder; 3-15% strontium sulfate. The present invention uses molybdenum powder and strontium sulfate as basic raw materials, which are low in cost; during vacuum hot pressing sintering, molybdenum and strontium sulfate generate SrMo5O8 phase, which has good high-temperature lubrication performance, and the SrMo5O8 phase is stable and not easy to decompose. The obtained molybdenum-based lubricating composite material has a low friction coefficient and wear rate at 600°C. The results of the embodiment show that at 600°C, the friction coefficient and wear rate of the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention are 0.21-0.23 and (0.52-0.76)×10 -14 m 3 ·N -1 ·m -1 between.
[0024] The present invention provides a method for preparing the molybdenum-based lubricating composite material containing SrMo5O8. The method adopts ball milling+pressing molding+vacuum hot pressing sintering, which is simple to operate and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The X-ray diffraction patterns of the mixed raw material powders of Examples 1 to 4 and Comparative Example 1;
[0026] Figure 2 The X-ray diffraction patterns of the lubricating composite materials obtained after sintering of Examples 1 to 4 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0027] The present invention provides a molybdenum-based lubricating composite material containing SrMo5O8, which is prepared from the following raw materials in percentage by mass:
[0028] Molybdenum powder 85-97%;
[0029] Strontium sulfate 3-15%.
[0030] In terms of mass percentage, the raw material for preparing the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention comprises 85-97% molybdenum powder, preferably 90-95%. In the present invention, the particle size of the molybdenum powder is preferably 15-75 μm, more preferably 30-50 μm. In the present invention, the purity of the molybdenum powder is preferably ≥99.5%.
[0031] The raw material for preparing the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention comprises 3-15% strontium sulfate, preferably 5-10%, in terms of mass percentage. In the present invention, the particle size of the strontium sulfate is preferably 15-75 μm, more preferably 30-50 μm. In the present invention, the purity of the strontium sulfate is preferably ≥99.7%.
[0032] In the present invention, the phase of the molybdenum-based lubricating composite material containing SrMo5O8 preferably includes a SrMo5O8 phase and a Mo phase. In the present invention, the mass percentage of the SrMo5O8 phase in the molybdenum-based lubricating composite material containing SrMo5O8 is preferably 5.65-21.80%, more preferably 9.02-19.42%; the mass percentage of the Mo phase is preferably 72.20-94.35%, more preferably 80.58-90.98%.
[0033] In the present invention, when the content of the strontium sulfate raw material is 15%, a new phase SrMoO4 appears in the molybdenum-based lubricating composite material containing SrMo5O8. At this time, the physical phase of the sintered composite material is composed of Mo phase, SrMo5O8 phase and SrMoO4 phase, the mass fraction of SrMo5O8 phase is 21.80%, the mass fraction of Mo phase is 72.20%, and the mass fraction of SrMoO4 phase is 6.00%.
[0034] In the present invention, the phase content of the molybdenum-based lubricating composite material is obtained according to XRD semi-quantitative analysis.
[0035] In the present invention, the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention has a friction coefficient of 0.21 to 0.23 at 600°C and a wear rate of (0.52 to 0.76)×10 -14 m 3 ·N -1 ·m -1 between.
[0036] The present invention provides a method for preparing the above-mentioned molybdenum-based lubricating composite material containing SrMo5O8, comprising the following steps:
[0037] The molybdenum powder and strontium sulfate are ball-milled to obtain a mixed powder;
[0038] The mixed powder is pressed and vacuum hot-pressed in sequence to obtain a molybdenum-based lubricating composite material containing SrMo5O8.
[0039] The present invention ball-mills molybdenum powder and strontium sulfate to obtain mixed powder. In the present invention, the ball milling is preferably carried out in a planetary high-energy ball mill.
[0040] In the present invention, the ball milling is preferably wet ball milling, and the dispersion medium of the wet ball milling is ethanol; in the present invention, the ball milling medium is preferably stainless steel balls with a diameter of 3 to 20 mm, and the ball-to-material ratio is preferably 5 to 15:1, and more preferably 8 to 12:1.
[0041] In the present invention, the ball milling speed is preferably 200 to 450 rpm, more preferably 250 to 400 rpm; the time is preferably 10 to 40 h, more preferably 20 to 30 h.
[0042] After the ball milling, the mixed powder is preferably dried. In the present invention, the drying method is preferably oven drying.
[0043] After obtaining the mixed powder, the present invention sequentially performs compression molding and vacuum hot pressing sintering on the mixed powder to obtain a molybdenum-based lubricating composite material containing SrMo5O8. The present invention preferably performs compression molding in a graphite mold, the compression molding temperature is preferably room temperature, the pressure is preferably 5 to 10 MPa, more preferably 6 to 8 MPa, and the time is preferably 20 to 40 seconds, more preferably 25 to 35 seconds.
[0044] In the present invention, the vacuum hot pressing sintering is preferably carried out in a vacuum hot pressing sintering furnace. In the present invention, the temperature of the vacuum hot pressing sintering is preferably 1100-1300°C, more preferably 1150-1250°C; the pressure is preferably 20-30MPa, more preferably 25MPa; the heat preservation and pressure holding time is preferably 30-120min, more preferably 60-90min; in the present invention, the heating rate to the vacuum hot pressing sintering temperature is preferably 5-15°C / min, more preferably 8-10°C / min. In the present invention, the vacuum degree of the vacuum hot pressing sintering is preferably ≤1.0×10 -2 Pa.
[0045] In the present invention, during the vacuum hot pressing sintering process, strontium sulfate decomposes to form SrO, SO2 and O2. In an environment composed of O2 and SO2, Mo is oxidized to form molybdenum oxide, which then reacts with SrO to form SrMo5O8. As the content of O2 and SO2 increases, that is, when the content of strontium sulfate raw material is ≥15wt%, a diffraction peak of SrMoO4 appears, and the physical phase of the sintered composite material is composed of Mo, SrMo5O8 and SrMoO4. As the content of strontium sulfate further increases, the content of the new phase SrMoO4 also increases, resulting in a decrease in the lubrication performance of the molybdenum-based lubricating composite material at 600°C.
[0046] After the vacuum hot pressing sintering is completed, the present invention preferably cools the obtained molybdenum-based lubricating composite material containing SrMo5O8. The present invention has no special requirements for the cooling method, and a cooling method well known to those skilled in the art can be used, such as cooling to room temperature with the furnace.
[0047] The molybdenum-based lubricating composite material containing SrMo5O8 and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0048] Example 1
[0049] A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof are prepared from the following raw materials in percentage by mass:
[0050] 75μm molybdenum powder 97%;
[0051] 75 μM Strontium sulfate 3%.
[0052] The preparation method comprises the following steps:
[0053] (1) Molybdenum powder and 3% strontium sulfate are mixed, mixed with ethanol in a planetary high-energy ball mill, and ball-milled at a speed of 450 rpm for 40 hours. The grinding balls used in the ball milling are stainless steel balls with a diameter of 3 to 20 mm, and the ball-to-material ratio is 15:1. After the ball milling is completed, it is dried and baked to obtain a mixed powder.
[0054] (2) placing the mixed powder into a graphite mold, and pressing and molding at room temperature and a pressure of 5 MPa for 40 seconds to obtain a molding material; placing the graphite mold containing the molding material into a vacuum hot pressing sintering furnace and evacuating the vacuum to an absolute pressure of 1.0×10 -2 Pa, then heated to 1300℃, heating rate 5℃ / min, applied positive pressure 20MPa after reaching the set temperature, kept warm and pressure for 30min, cooled to room temperature with the furnace, and obtained a molybdenum-based lubricating composite material containing SrMo5O8, recorded as Mo-3SrSO4. The phase content of the Mo-3SrSO4 composite material after sintering was calculated as follows: the mass fraction of SrMo5O8 phase was 5.65%, and the mass fraction of Mo phase was 94.35%.
[0055] Example 2
[0056] A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof are prepared from the following raw materials in percentage by mass:
[0057] 15μm molybdenum powder 95%;
[0058] 15 μM Strontium sulfate 5%.
[0059] The preparation method comprises the following steps:
[0060] (1) Molybdenum powder and 5% strontium sulfate are mixed, mixed with ethanol in a planetary high-energy ball mill, and ball-milled at a speed of 200 rpm for 10 hours. The grinding balls used in the ball milling are stainless steel balls with a diameter of 3 to 20 mm, and the ball-to-material ratio is 5:1. After the ball milling is completed, it is dried and baked to obtain a mixed powder.
[0061] (2) placing the mixed powder into a graphite mold, pressing and molding at room temperature and a pressure of 10 MPa for 20 seconds to obtain a molding material; placing the graphite mold containing the molding material into a vacuum hot pressing sintering furnace and evacuating the vacuum to an absolute pressure of 1.0×10 -2Pa, then heated to 1200℃, heating rate 10℃ / min, applied positive pressure 30MPa after reaching the set temperature, kept warm and pressure for 60min, cooled to room temperature with the furnace, and obtained a molybdenum-based lubricating composite material containing SrMo5O8, recorded as Mo-5SrSO4. The phase content of the Mo-5SrSO4 composite material after sintering was calculated as follows: the mass fraction of SrMo5O8 phase was 9.02%, and the mass fraction of Mo phase was 90.98%.
[0062] Example 3
[0063] A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof are prepared from the following raw materials in percentage by mass:
[0064] 45μm molybdenum powder 90%;
[0065] 75 μM Strontium sulfate 10%.
[0066] The preparation method comprises the following steps:
[0067] (1) Molybdenum powder and 10% strontium sulfate are mixed, mixed with ethanol in a planetary high-energy ball mill, and ball-milled at a speed of 350 rpm for 30 hours. The grinding balls used in the ball milling are stainless steel balls with a diameter of 3-20 mm, and the ball-to-material ratio is 10:1; after the ball milling is completed, it is dried and baked to obtain a mixed powder.
[0068] (2) placing the mixed powder into a graphite mold, pressing and molding at room temperature and a pressure of 10 MPa for 30 seconds to obtain a molding material; placing the graphite mold containing the molding material into a vacuum hot pressing sintering furnace and evacuating the vacuum to an absolute pressure of 1.0×10 -2 Pa, then heated to 1100℃, heating rate 15℃ / min, applied positive pressure 25MPa after reaching the set temperature, kept warm and pressure for 90min, cooled to room temperature with the furnace, and obtained a molybdenum-based lubricating composite material containing SrMo5O8, recorded as Mo-10SrSO4. The phase content of the Mo-10SrSO4 composite material after sintering was calculated as follows: the mass fraction of SrMo5O8 phase was 19.42%, and the mass fraction of Mo phase was 80.58%.
[0069] Example 4
[0070] A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof are prepared from the following raw materials in percentage by mass:
[0071] 30μm molybdenum powder 85%;
[0072] 15 μM Strontium sulfate 15%.
[0073] The preparation method comprises the following steps:
[0074] (1) Molybdenum powder and 15% strontium sulfate are mixed, mixed with ethanol in a planetary high-energy ball mill, and ball-milled at a speed of 300 rpm for 20 hours. The grinding balls used in the ball milling are stainless steel balls with a diameter of 3 to 20 mm, and the ball-to-material ratio is 12:1. After the ball milling is completed, it is dried and baked to obtain a mixed powder.
[0075] (2) placing the mixed powder into a graphite mold, pressing and molding at room temperature and a pressure of 8 MPa for 30 seconds to obtain a molding material; placing the graphite mold containing the molding material into a vacuum hot pressing sintering furnace and evacuating the vacuum to an absolute pressure of 1.0×10 -2 Pa, then heated to 1100℃, heating rate 10℃ / min, applied positive pressure 20 after reaching the set temperature, kept warm and pressure for 120min, cooled to room temperature with the furnace, and obtained a molybdenum-based lubricating composite material containing SrMo5O8, recorded as Mo-15SrSO4. The phase content of the Mo-15SrSO4 composite material after sintering was calculated as follows: the mass fraction of SrMo5O8 phase was 21.80%, the mass fraction of Mo phase was 72.20%, and the mass fraction of SrMoO4 phase was 6.00%.
[0076] Comparative Example 1
[0077] A molybdenum-based lubricating composite material containing SrMo5O8 and a preparation method thereof are prepared from the following raw materials in percentage by mass:
[0078] 60μm molybdenum powder 82%;
[0079] 30 μm Strontium sulfate 18%.
[0080] The preparation method comprises the following steps:
[0081] (1) Molybdenum powder and 18% strontium sulfate are mixed, mixed with ethanol in a planetary high-energy ball mill, and ball-milled at a speed of 350 rpm for 25 hours. The grinding balls used in the ball milling are stainless steel balls with a diameter of 3 to 20 mm, and the ball-to-material ratio is 8:1. After the ball milling is completed, it is dried and baked to obtain a mixed powder.
[0082] (2) placing the mixed powder into a graphite mold, pressing and molding at room temperature and a pressure of 10 MPa for 30 seconds to obtain a molding material; placing the graphite mold containing the molding material into a vacuum hot pressing sintering furnace and evacuating the vacuum to an absolute pressure of 1.0×10 -2Pa, then heated to 1100℃, heating rate 8℃ / min, applied positive pressure 25MPa after reaching the predetermined temperature, kept warm and pressure for 100min, cooled to room temperature with the furnace, and obtained a molybdenum-based lubricating composite material containing SrMo5O8, recorded as Mo-18SrSO4. The phase contents of the Mo-18SrSO4 composite material were calculated as follows: the mass fraction of the SrMo5O8 phase was 25.88%, the mass fraction of the Mo phase was 63.60%, and the mass fraction of the SrMoO4 phase was 10.52%.
[0083] Performance Testing
[0084] X-ray diffraction analysis was performed on the mixed raw material powders of Examples 1 to 4 and Comparative Example 1 and the lubricating composite material after sintering. The X-ray diffraction spectrum of the mixed raw material powder is as follows: Figure 1 As shown, the X-ray diffraction pattern of the obtained metal-based solid lubricating composite material is as follows Figure 2 As shown. Figure 1 and Figure 2 It can be seen that when the strontium sulfate content is in the range of 3-10wt%, SrMo5O8 phase appears in the lubricating composite material after sintering; when the strontium sulfate content is ≥15wt%, a new phase SrMoO4 appears in the lubricating composite material after sintering, and the phase of the sintered lubricating composite material is composed of Mo phase, SrMo5O8 phase and SrMoO4 phase.
[0085] The friction coefficient and wear rate of the lubricating composite materials obtained in Examples 1 to 4 and Comparative Example 1 were tested, and the results are listed in Table 1. The test conditions were: load 10N, frequency 5Hz, sliding distance 1mm, test temperature 600°C, and test time 1h.
[0086] Table 1 Friction coefficient and wear rate of the lubricating composite materials obtained in Examples 1 to 4 and Comparative Example 1
[0087] project Test temperature Friction coefficient Wear rate / (10-14m3·N-1·m-1) Example 1 600℃ 0.23 0.76 Example 2 600℃ 0.23 0.68 Example 3 600℃ 0.21 0.52 Example 4 600℃ 0.23 0.66 Comparative Example 1 600℃ 0.24 0.96
[0088] It can be seen from Table 1 that the friction coefficient of the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention at 600°C is between 0.21 and 0.23, and the wear rate is between (0.52 and 0.76)×10 -14 m 3 ·N -1 ·m -1 between.
[0089] Comparative Example 2
[0090] Taking the Ni-Mo-SrSO4 lubricating composite material prepared in the metal-based solid lubricating composite material containing strontium molybdate and strontium nickel molybdate disclosed in patent CN202110515241.X and the preparation method thereof as a comparative example, the friction coefficient and wear rate thereof were tested, and the results are listed in Table 2. The test conditions are: load 10N, frequency 5Hz, sliding distance 1mm, test temperature 600℃, and test time 1h.
[0091] Table 2 Friction coefficient and wear rate of Ni-Mo-SrSO4 lubricated composites
[0092] Element Test temperature Friction coefficient Wear rate / (10-14m3·N-1·m-1) Ni-13Mo-5SrSO4 600℃ 0.63 10.62 Ni-8Mo-7SrSO4 600℃ 0.59 15.56 Ni-15Mo-6SrSO4 600℃ 0.68 6.98 Ni-14.25Mo-5SrSO4 600℃ 0.69 7.56 Ni-4.75Mo-5SrSO4 600℃ 0.42 32.46 Ni-19Mo-5SrSO4 600℃ 0.65 8.59
[0093] It can be seen from Table 2 that the friction coefficient of Ni-Mo-SrSO4 lubricated composite materials is between 0.42 and 0.69, and the wear rate is between (6.98 and 32.46)×10 -14 m 3 ·N -1 ·m -1 The lubrication performance of the molybdenum-based lubricating composite material containing SrMo5O8 provided by the present invention at 600°C is significantly higher than that of the metal-based solid lubricating composite material containing strontium molybdate and strontium nickel molybdate disclosed in patent CN202110515241.X.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of a molybdenum-based lubricating composite material containing SrMo5O8 as a lubricating material, wherein the application temperature is 600°C; the molybdenum-based lubricating composite material containing SrMo5O8 is prepared from the following raw materials in percentage by mass: Molybdenum powder 85-97%; Strontium sulfate 3-15%; The mass percentage of the SrMo5O8 phase in the molybdenum-based lubricating composite material containing SrMo5O8 is 5.65-21.80%.
2. The use according to claim 1, characterized in that: The molybdenum-based lubricating composite material containing SrMo5O8 is prepared from the following raw materials in percentage by mass: Molybdenum powder 90-95%; Strontium sulfate 5-10%.
3. The use according to claim 1 or 2, characterized in that: The particle size of the molybdenum powder is 15-75 μm, and the purity is ≥99.5%; the particle size of the strontium sulfate is 15-75 μm, and the purity is ≥99.7%.
4. The use according to claim 1, characterized in that: The preparation method of the molybdenum-based lubricating composite material containing SrMo5O8 comprises the following steps: The molybdenum powder and strontium sulfate are ball-milled to obtain a mixed powder; The mixed powder is pressed and vacuum hot-pressed in sequence to obtain a molybdenum-based lubricating composite material containing SrMo5O8.
5. The use according to claim 4, characterized in that: The ball milling is wet ball milling, the dispersion medium of the wet ball milling is ethanol, and the ball-to-material ratio is 5 to 15:
1.
6. The use according to claim 4 or 5, characterized in that: The ball milling speed is 200-450 rpm, and the time is 10-40 hours.
7. The use according to claim 4, characterized in that: The pressure of the pressing molding is 5-10 MPa, and the time is 20-40 seconds.
8. The use according to claim 4, characterized in that: The vacuum hot pressing sintering temperature is 1100-1300° C., the pressure is 20-30 MPa, the heat preservation and pressure holding time is 30-120 min, and the heating rate is 5-15° C. / min.
9. The use according to claim 4 or 8, characterized in that: The vacuum degree of the vacuum hot pressing sintering is ≤1.0×10 -2 Pa.
Citation Information
Patent Citations
Metal-based solid lubricating composite material containing strontium molybdate and strontium nickel molybdate and preparation method thereof
CN113215446A